Oviposition Deterrent and Insecticidal Activities of Some Indigenous Plant Extracts against the Rice Moth, Corcyra cephalonica (Stainton) - Narangoda, S.R.C.N.K.; Karunaratne, M.M.S.C. (My University, 2009)
Methanol extracts of eighteen plants belonging to thirteen families were evaluated under laboratory conditions for their effects on the oviposition and larval mortality of the rice moth, Corcyra cephalonica. Each plant extract was tested at a concentration of 12g11.All the extracts tested showed significant variations in toxic and oviposition deterrence against C. cephalonica when compared with the control. However, among the eighteen plants evaluated, leaf and seed extracts of Azadiracta indica and the seed extract of Piper nigrum were found to be the most effective causing 100% larval mortality. This was followed by leaf (81 %) and seed (84%) extracts of Annona squamosa. Conversely, the seed extract of Annona muricata was the least toxic exhibiting only 2.83 % mortality. More over, maximum ovipostion deterrence was observed with P nigrum followed by A. indica and A. squamosa. None of the plant extracts had any adverse effects on the viability of maize seeds. When percentage mortality and ovipositional deterrence were considered as indices of insecticidal activity, P. nigrum and A. indica together with A. squamosa proved to be the most effective plant materials that could be used as grain protectants in controlling infestations of C. cephalonica.
Keywords: Plant extracts; Corcyra cephalonica; Rice moth; larval mortality; Oviposition deterrence